PENGARUH RETURN ON ASSET (ROA), CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER), DAN PRICE TO BOOK VALUE (PBV) TERHADAP HARGA SAHAM - Liskan Kirana; Ronny Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT This research was conducted with the aim of analyzing how the influence of Return on Assets (ROA), Current Ratio (CR), Debt To Equity Ratio (DER), and Price To Book Value (PBV) Against Stock Prices. The sample in this study were 23 manufacturing companies in the consumer goods industry sector. The analysis method used in this study is Multiple Linear Regression with the SPSS Version 22 For Windows application. Based on the results of the hypothesis test it is obtained that the test results simultaneously show the value of Return On Assets (ROA), Current Ratio (CR), Debt To Equity Ratio (DER) and Price To Book Value (PBV) affect stock prices, and Price To Book Value (PBV). The partial test results show that Return on Assets (ROA) has a positive effect on the stock price of consumer goods companies, Current Ratio (CR) has a negative effect on the stock price of consumer goods companies. Debt to Equity Ratio (DER) has a negative effect on the stock price of consumer goods companies. . Price to Book Value (PBV) has a positive effect on the stock price of consumer goods companies.Keywords:Return On Asset; Current Ratio; Debt to Equity Ratio; Price to Book Value; Stock Price